Fruit Sorting System for Oranges Based on Size and Color Using Fuzzy Logic - Ali Rizal Chaidir; Panji Eka Prasetya; Arizal Mujibtamala Nanda Imron; Immawan Wicaksono; Guido Dias Kalandro; Gramandha Wega Intyanto (Fakultas Teknik Universitas PGRI Banyuwangi, 2024)
Along with advances in technology, the use of human labor in managing agricultural products is decreasing because it has been replaced by robots. Robots perform better than human workers who have emotions and need time to rest. This can cause errors when sorting fruit due to lack of concentration caused by fatigue. The large harvest of oranges takes a long time to sort them, starting from color, size, weight, and price, before they are marketed. To make it easier for farmers to sort their harvest from orange fruit, this research was created titled